Treatment efficacy for non-cardiovascular chest pain: a systematic review and meta-analysis. - Jakob M Burgstaller; Boris F Jenni; Johann Steurer; Ulrike Held; Maria M Wertli (PLoS ONE)
Background Non-cardiovascular chest pain (NCCP) leads to impaired quality of life and is associated with a high disease burden. Upon ruling out cardiovascular disease, only vague recommendations exist for further treatment. Objectives To summarize treatment efficacy for patients presenting with NCCP. Methods Systematic review and meta-analysis. In July 2013, Medline, Web of Knowledge, Embase, EBSCOhost, Cochrane Reviews and Trials, and Scopus were searched. Hand and bibliography searches were also conducted. Randomized controlled trials (RCTs) evaluating non-surgical treatments in patients with NCCP were included. Exclusion criteria were poor study quality and small sample size (<10 patients per group). Results Thirty eligible RCT's were included. Most studies assessed PPI efficacy for gastroesophageal reflux disorders (GERD, n = 10). Two RCTs included musculoskeletal chest pain, seven psychotropic drugs, and eleven various psychological interventions. Study quality was high in five RCTs and acceptable in 25. PPI treatment in patients with GERD (5 RCTs, 192 patients) was more effective than placebo [pooled OR 11.7 (95% CI 5.5 to 25.0, heterogeneity I2 = 6.1%)]. The pooled OR in GERD negative patients (4 RCTs, 156 patients) was 0.8 (95% CI 0.2 to 2.8, heterogeneity I2 = 50.4%). In musculoskeletal NCCP (2 RCTs, 229 patients) manual therapy was more effective than usual care but not than home exercise [pooled mean difference 0.5 (95% CI -0.3 to 1.3, heterogeneity I2 = 46.2%)]. The findings for cognitive behavioral treatment, serotonin reuptake inhibitors, tricyclic antidepressants were mixed. Most evidence was available for cognitive behavioral treatment interventions. Limitations Only a small number of studies were available. Conclusions Timely diagnostic evaluation and treatment of the disease underlying NCCP is important. For patients with suspected GERD, high-dose treatment with PPI is effective. Only limited evidence was available for most prevalent diseases manifesting with chest pain. In patients with idiopathic NCCP, treatments based on cognitive behavioral principles might be considered.